2014
DOI: 10.1016/j.earscirev.2014.01.006
|View full text |Cite
|
Sign up to set email alerts
|

The process of ghost-rock karstification and its role in the formation of cave systems

Abstract: This paper presents an extensive review of the process of ghost-rock karstification and highlights its role in the formation of cave systems. The process integrates chemical weathering and mechanical erosion and extends a number of existing theories pertaining to continental landscape development. It is a two stage process that differs in many respects from the traditional single-stage process of karstification by total removal. The first stage is characterised by chemical dissolution and removal of the solubl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(44 citation statements)
references
References 47 publications
1
40
0
3
Order By: Relevance
“…An alternative explanation (Bła _ zejowski and Walsh, 2013;Rowberry et al, 2014) is that the lamination is inherited from decalcified limestone, with the blocks as less weathered relicts. Such textures are termed ghost karst (Dubois et al, 2014). The context of the residual deposits at Bullslaughter Bay is discussed later (Section 9).…”
Section: Residual Deposits From Weathering Overprintmentioning
confidence: 98%
“…An alternative explanation (Bła _ zejowski and Walsh, 2013;Rowberry et al, 2014) is that the lamination is inherited from decalcified limestone, with the blocks as less weathered relicts. Such textures are termed ghost karst (Dubois et al, 2014). The context of the residual deposits at Bullslaughter Bay is discussed later (Section 9).…”
Section: Residual Deposits From Weathering Overprintmentioning
confidence: 98%
“…These fractures have been recognized across the carbonate Jurassic and Cretaceous rocks. Late Jurassic rocks can also be karstified with ghost rocks (Dubois et al, 2014) in the deep part of the aquifer, as observed in the current vadose zone. The whole aquifer is then cross-cut by karst features forming an extensive interconnected karst network.…”
Section: How Has Geological Evolution Structured the Aquifer?mentioning
confidence: 99%
“…It is important for economic and social development, agricultural production, and ecological restoration (Keshavarzi et al, 2006;Hannu and Bjørn, 2010;Johan et al, 2010;Vialle et al, 2011). In karst mountainous territories, Due to the extensive development of underground fissures, pipeline, caves and underground streams causes surface water scarcity, with water rapidly infiltrating underground through the network of karst fissures and conduits in the rock mass (White, 1988;Ford and Williams, 2007;Williams, 2008;Lopez et al, 2009;Brinkmann and Parise, 2012;Bai et al, 2013;Dubois et al, 2014). The shortage of surface water is a major bottleneck in ecological restoration and sustainable development of economy and society (Aley, 2000;Parise and Sammarco, 2014).…”
Section: Introductionmentioning
confidence: 96%